Extrachromosomal circular DNA of tandemly repeated genomic sequences in Drosophila. - Cohen, S.; Yacobi, K.; Segal, D. (Genome Research, 2003)
One characteristic of genomic plasticity is the presence of extrachromosomal circular DNA (eccDNA). This DNA is found in various eukaryotes from yeast to humans, and its levels are elevated by exposure to carcinogens. eccDNA is heterogeneous in size and composed of chromosomal sequences. In this study we used two-dimensional gel electrophoresis to detect and characterize eccDNA in Drosophila. We found eccDNA throughout the fly's life cycle. These molecules comprise up to 10% of the total repetitive DNA content, and their size ranges from <1 kb to >20 kb. The eccDNA population contains circular multimers of tandemly repeated genes such as histones, rDNA, Stellate, and the Suppressor of Stellate. Multimers of centromeric heterochromatin sequences are included in eccDNA as well. Our findings are consistent with the hypothesis that intramolecular homologous recombination between direct tandem repeats is a favorite mechanism for eccDNA formation. The level of eccDNA increased following MMS treatment of wild-type larvae, consistent with phenomena observed in cultured mammalian cells. This shows mutagen-induced eccDNA formation in the context of the whole organism for the first time. Mutations in the genes okra, mus309, and mei41 did not affect eccDNA under normal conditions or following mutagen treatment, implying that eccDNA formation is different from known pathways of DNA repair.